Regulasi Emosi pada Anak dalam Perspektif Islam - Linda Muliasari (Gunung Djati Conference Series, 2023)
This research is focused on the emotions of early childhood, by overcoming and understanding what children feel and how to overcome them, this research uses a qualitative method by trying to apply descriptive data - analysis. The purpose of this study was to determine the ability of each child to control emotions and apply them in everyday life. The results of the study show that people who suppress angry emotions are recognized as great human beings and will receive rewards from God. This research concludes that learning emotion regulation is very important for children to be responsible when they are adults, and children can know emotions, several cases occurred when I saw on social media a mother and father giving an understanding of their emotions, this can be emulated and imitated. Apply it so that children can control their emotions.